(untitled) (Journal of the College of Basic Education, 2026)
The pursuit of self-transcendence involves setting sometimes unrealistically high expectations for oneself and others, often with the goal of perfection. Some individuals may focus on their inability to meet their high standards and as a result feel dissatisfied, frustrated, express the need to work harder, or lose their ability to meet certain expectations in their lives. Therefore, the aim of the current research is to identify self-transcendence among educational counselors and to identify the significance of differences in self-transcendence among educational counselors according to the gender variable (males - females). The research scale in its final form consisted of (24) paragraphs, where the reliability coefficient by the retest method reached (0.74) and the reliability coefficient by the Cronbach’s alpha method reached (0.70). The research was limited to educational counselors in the education directorates of Baghdad Governorate for the academic year 2025/2026. The research community consisted of (2899) educational counselors, male and female, so the number of individuals in the research sample reached (400) male and female counselors. The researcher adopted the descriptive approach, and applied the research scale, then the data were analyzed using the statistical package (SPSS). The results showed that educational counselors enjoy: self-transcendence, and females outperform males in self-transcendence. According to the results, some recommendations and suggestions were presented.